Time to live with the new normal - Ahmad, Zeti Azreen (IIUMToday, 2020)
The government’s decision to implement the conditional movement control order (CMCO) has received mix reactions from netizens and public at large. Some applauded the decision as it will enable them to continue working, while not few are worried that such decision would trigger COVID-19 cases to spike again. Similarly, health experts have also voiced their concern that this abrupt move might lead to third wave of infection.